Burden of Respiratory Syncytial Virus Hospitalizations in Canada - Ian Mitchell; Isabelle Defoy; ElizaBeth Grubb (Canadian Respiratory Journal)
Objective. To examine the socioeconomic burden of respiratory syncytial virus (RSV) disease for Canadian infants hospitalized for the condition. Data and Methods. The descriptive study used data collected in Alberta, Canada, during 2 consecutive RSV seasons. Infants (<1 year of age) were included if they had not received palivizumab and were hospitalized with a confirmed diagnosis of RSV. Hospitalization resource use and parental time burden, out-of-pocket costs, lost work productivity, and stress and anxiety were assessed. Results. 13.4% of all infants (n = 67) had intensive care unit (ICU) admission, and average ICU stay for these infants was 6.5 days. Families had average out-of-pocket expenses of 736.69 Canadian dollars (CAD $), and the average time both parents spent in hospital was nearly 7 days (164.0 hours). For working parents (n = 43), average absenteeism was 49% and overall work impairment was 77.8%. Parents also exhibited significant parental stress (3.6 on the Parental Stressor Scale: 43.9 state anxiety and 36.9 trait anxiety scores). Conclusions. Results indicate a high burden associated with the hospitalization of an infant due to RSV disease in terms of resource use, time, productivity, costs, and stress, even among a population of infants not considered to be at risk for the condition.